Interleukin-35 Suppresses Antiviral Immune Response in Chronic Hepatitis B Virus Infection - Shao, Xue; Ma, Jingting; Jia, Shengnan; Yang, Lanlan; Wang, Wudong; Jin, Zhenjing (Frontiers in Cellular and Infection Microbiology, 2017)
The mechanisms of hepatitis B virus (HBV) persistent infection are not completely understood. Interleukin (IL)-35, which is a newly identified cytokine belongs to IL-12 family, has been demonstrated to induce immunotolerance. Thus, the aim of current study was to investigate the role of IL-35 during chronic HBV infection. A total of 61 patients with chronic HBV infection [37 chronic hepatitis B (CHB) and 24 asymptomatic HBV carriers (ASC)] and 20 healthy individuals were enrolled. IL-35 concentration as well as the modulatory function of IL-35 on CD4+CD25+CD127dim/− regulatory T cells (Tregs) and on HBV antigen-specific CD8+ T cells was investigated. IL-35 expression was significantly increased in both CHB and ASC, and was positively correlated with the levels of HBV DNA. Inhibition of viral replication induced the reduction in serum levels of IL-35. IL-35 stimulation led to inhibition of proinflammatory cytokine productions and elevation of apoptosis in peripheral blood mononuclear cells (PBMCs), but not in HepG2.2.15 cells. Moreover, IL-35 stimulation not only robustly inhibited cellular proliferation, but also up-regulated the production of IL-10 and IL-35 in a HBV antigen-specific and non-specific manner in Tregs/CD4+CD25− T cells coculture system, which indicated enhancement of suppressive function of Tregs. Furthermore, IL-35 also reduced both cytolytic activity (direct lysis of HepG2.2.15 cells) and noncytolytic function (IFN-γ and TNF-α production) of HBV antigen-specific CD8+ T cells. The current data suggested that IL-35 contributed to maintain viral persistence by suppressing antiviral immune responses and reducing inflammatory responses in chronic HBV infection.